2010
DOI: 10.1103/physrevb.82.165405
|View full text |Cite
|
Sign up to set email alerts
|

Complex edge effects in zigzag graphene nanoribbons due to hydrogen loading

Abstract: We have performed density functional calculations as well as employed a tight-binding theory, to study the effect of passivation of zigzag graphene nanoribbons (ZGNR) by Hydrogen. We show that each edge C atom bonded with 2 H atoms open up a gap and destroys magnetism for small widths of the nanoribbon. However, a re-entrant magnetism accompanied by a metallic electronic structure is observed from 8 rows and thicker nanoribbons. The electronic structure and magnetic state are quite complex for this type of ter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 28 publications
8
59
1
Order By: Relevance
“…One can see that a sharp conductance peak presents right at the Fermi level of the H-zGNR as the result of the highly conductive edge states [3]. A gap about 0.48 eV presents around the Fermi level of the H2-zGNR as expected [24]. By introducing sp 3 -edges ðN H2 Þ in a pure sp 2 -edges, the conductance spectra show two drastic changes, namely the significant decrease of the conductance around the Fermi level and the presence of some conductance dips.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…One can see that a sharp conductance peak presents right at the Fermi level of the H-zGNR as the result of the highly conductive edge states [3]. A gap about 0.48 eV presents around the Fermi level of the H2-zGNR as expected [24]. By introducing sp 3 -edges ðN H2 Þ in a pure sp 2 -edges, the conductance spectra show two drastic changes, namely the significant decrease of the conductance around the Fermi level and the presence of some conductance dips.…”
Section: Resultsmentioning
confidence: 63%
“…While H2-terminations can only induce a band gap in ultrathin H2-zGNRs. Such a gap rapidly decreases to zero when the width increases to only 7-zigzag rows (about 1.5 nm) [24]. At the same time, the zGNRs with mixed H-and H2-terminations have also been studied [26][27][28].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…selective doping [9], edge modulation (defective boundaries and edge disorder) [10,11], enabling each edge Carbon (C) atom to two Hydrogen (H) atoms [12], terminating the edge C atoms of the ribbon by Nitrogen (N) atoms [13].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Concerning the former, first principles electronic structure calculations and experiments have reported that graphene can be transformed into an insulating sheet, named graphane, 15 by complete hydrogenation. Graphane has been recently synthesized by Elias et al, 9 following initial predictions by Sofo et al 15 Quantum confinement effects have also shown the possibilities of band gap engineering, as in graphene nanoribbons [24][25][26][27] and nanomeshes 28 passivated with hydrogen. However, the resulting electronic properties are strongly dependent on the type of edge termination.…”
Section: Introductionmentioning
confidence: 99%